Mental stress and the risks of metabolic syndrome and related components in military personnel: CHIEF cohort study - Kun-Zhe Tsai; Kun-Zhe Tsai; Kun-Zhe Tsai; Ko-Huan Lin; Ai-Hsiu Hung; Yun-Chen Chang; Yun-Chen Chang; Xuemei Sui; Carl J. Lavie; Gen-Min Lin; Gen-Min Lin (Frontiers in Cardiovascular Medicine)
BackgroundThe association observed between mental stress and metabolic syndrome (MetS) has varied across studies and may be confounded by physical activity (PA) and fitness status.MethodThis study included a military cohort of 2,854 participants in Taiwan who were not taking any medications and were free of baseline MetS. The Brief Symptoms Rating Scale (BSRS-5) includes five domains—depression, anxiety, hostility, insomnia, and interpersonal sensitivity—measured on a five-point Likert-type scale ranging from 0 to 4, with a maximum score of 20. PA (hrs/wk) was categorized into three levels: <150, 150–299 and ≥300. Aerobic fitness was evaluated by the amount of time taken to complete a 3,000 m run. MetS was defined according to the International Diabetes Federation (IDF) criteria. Multivariable Cox proportional hazards regression analysis with adjustments for potential covariates including PA and aerobic fitness was utilized to determine the associations of BSRS-5 scores (each 1-unit score increase) with the incidence of MetS and related features.ResultsDuring a median follow-up period of 5.8 years, 662 new-onset cases of MetS (23.2%) developed. BSRS-5 scores were not associated with the risk of new-onset MetS [hazard ratio (HR): 1.006 [95% confidence interval (CI): 0.975, 1.039]]. Among the five MetS features, the only one associated with BSRS-5 scores was the risk of new-onset hypertension [HR: 1.038 (95% CI: 1.002, 1.075)], which was defined as blood pressure ≥130/85 mmHg or the use of antihypertensive medications, among 2,405 participants free of baseline hypertension.ConclusionsOur findings suggest that in young adult military personnel, mental stress was not associated with the incidence of MetS but was associated with its hypertension component, which was independent of PA and aerobic fitness.